Дослідження ефективності методів та засобів зберегання і розподілення даних у NOSQL сховищах - Омельченко, В. О. (ХНУРЕ, 2021)
This paper investigates the usage of methods for storage and data distribution. The need of big data research is fast growing industry. The amount of data itself that needs to be stored and analyzed is increasing every day, as well as the number of industries that need to store a large amount of information. The work is devoted to the study of the effectiveness of methods and tools for storing and distributing data in NoSQL storages.
Науковий керівник – к.т.н., проф. Лєсна Н. С.
Keywords: ефективность методів; дані у NOSQL сховищах